Facts about Wildlife Diseases: Highly Pathogenic Avian Influenza (HPAI) - Bridget B. Baker; Samantha Wisely (EDIS)
Avian influenza is a highly contagious respiratory virus that circulates globally among wild birds. As of July 2022, H5N1 has spread quickly in the United States, killing wild birds in more than 40 states and impacting more than 60 species. While lethal to many bird and some mammal species, the current circulating strain is not particularly infectious in humans.  Nonetheless, basic precautions are still warranted, particularly for those people in contact with wild birds via hunting or the use of backyard bird feeders or baths, as well as people with backyard poultry or pet birds. These basic precautions are detailed.